Formulation and evaluation of poly herbal hand wash gel containing essential oils - A. Mounika; Vijayanand P; V. Jyothi (International Journal of Pharmacy and Analytical Research, 2022)
The present research was aimed to evaluate the antibacterial efficacy of various herbal oils such as Cinnamon, eucalyptus, orange, peppermint; clove, geranium and rosemary oils found that cinnamon, geranium and peppermint showed better antibacterial, antimicrobial activities. The research was carried out to formulate and evaluate the poly herbal gels. Hand wash gel containing Cinnamon and geranium oil. The anti -microbial activity of the formulated herbal hand wash gel was te sted against Escherichia coli and Staphylococcus aureus by pour plate techniques and the results obtained were compared with commercial antibacterial standards. Also the efficiency was checked by using the hand wash gel on volunteers.